Role of the internet banking in the modern banking system - K. A. Babenko (Путеводитель предпринимателя)
The article examines the experience of the banks which provide internet banking services in Russia. The analysis of the development of such services in recent years is represented. On the basis of the obtained data the conclusion on the feasibility of such services in the modern world is made.